2016
DOI: 10.1111/gcb.13387
|View full text |Cite
|
Sign up to set email alerts
|

Conventional intensive logging promotes loss of organic carbon from the mineral soil

Abstract: There are few data, but diametrically opposed opinions, about the impacts of forest logging on soil organic carbon (SOC). Reviews and research articles conclude either that there is no effect, or show contradictory effects. Given that SOC is a substantial store of potential greenhouse gasses and forest logging and harvesting is routine, resolution is important. We review forest logging SOC studies and provide an overarching conceptual explanation for their findings. The literature can be separated into short-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 77 publications
(111 reference statements)
1
35
0
5
Order By: Relevance
“…Stand collapse associated with a rapid decline in ground water in the northern jarrah forest (200 km to the north of the karri forests) was recognised as trending southwards . Impacts of clear-felling on carbon stocks and the structural integrity of forests were quantified from local to global scales (Dean et al 2012(Dean et al , 2017. In addition, effects of warming and drying were assessed (Dean and Wardell-Johnson 2010) and retention of old-growth characteristics advocated:…”
Section: Advocacy In the Era Of Sustainabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Stand collapse associated with a rapid decline in ground water in the northern jarrah forest (200 km to the north of the karri forests) was recognised as trending southwards . Impacts of clear-felling on carbon stocks and the structural integrity of forests were quantified from local to global scales (Dean et al 2012(Dean et al , 2017. In addition, effects of warming and drying were assessed (Dean and Wardell-Johnson 2010) and retention of old-growth characteristics advocated:…”
Section: Advocacy In the Era Of Sustainabilitymentioning
confidence: 99%
“…However, regrowth is growing much more slowly than anticipated. (Schultz 2015, p. 1; SY23) This indicates the potential for regrowth forest under 50 years of age to have reduced capacity to regain the former height or biomass of the forest it replaced even if it were not logged again (Dean et al 2017). Alternative viewpoints assumed reduced rainfall as adequate to sustain karri forest (e.g.…”
Section: )mentioning
confidence: 99%
“…Muutuvad ka puit-ja rohttaimede osakaal ning mulla juurte sügavusjaotus, väheneb neto primaarproduktsioon ja suureneb leos tumine (L al et al, 2005). Majandamise mõju metsa mulla süsinikuvarudele ja CO 2 emiteerimisele varieerub suuresti, sõltudes raiest möödunud ajast, kliimavööndist, puu liigist, mullatüübist jne (nt Laporte et al, 2013;James & Harrison, 2016;Dean et al, 2017). Globaalses metaanalüüsis (Achat et al, 2015), kus analüüsiti raiejärgset mullasüsiniku muutumist rohkem kui 2000 alal kuni 135 aasta jooksul, leiti, et tavapärase raietsükli (lageraie ja harvendusraie) jooksul ei toimu kogu mullaprofi ili arvesse võttes olulisi süsiniku kadusid mullast.…”
Section: Metsade Majandamise Mõju Süsinikuringele Ja -Varudeleunclassified
“…Responses of SOC and TN stocks in surface and subsurface mineral soils may be particularly relevant in the context of timber harvesting, whose legacy effects may last for decades to centuries [ Chen et al , ; Kellman et al , ; Prest et al , ; Dean et al , ]. Both SOC and TN are important indicators of soil quality due to their ability to influence soil structure, nutrient concentrations, water‐holding capacity, and microbial activity [ Lal , ; Bationo et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…These reductions have been shown to be positively correlated to both the amount of harvested biomass removed and the C and N stores in that biomass [ Hazlett et al , ; Kellman et al , ; Vario et al , ; Achat et al , , ]. A recent literature review and modeling study has suggested that the observed wide range of SOC responses to forest harvest is likely due to variability in (a) the time interval between the harvest event and SOC sampling and (b) the number of prior logging cycles at a given site [ Dean et al , ]. It should also be noted that soil C has been shown to take several decades to recover to preharvest levels following harvest, with some soil orders taking upward of 75 years to recover [ James and Harrison , ]; however, continued research is needed to further investigate the mechanisms governing soil C recovery, especially at depth.…”
Section: Introductionmentioning
confidence: 99%